Review of the prevalence of postnatal depression across cultures - Mohd Arifin, Siti Roshaidai; Cheyne, Helen; Maxwell, Margaret (AIMS Press, 2018)
The purpose of this review was to examine articles related to recent epidemiological evidence of the prevalence of maternal postnatal depression (PND) across different countries and cultures and to identify specific epidemiological studies that have been carried out exclusively in Malaysia on the prevalence of maternal PND. The review was undertaken in two stages, an initial review and an updated review. At both stages systematic literature searches of online databases were performed to identify articles on the prevalence of maternal PND. A total of 124 articles concerning research conducted in more than 50 countries were included in the final analysis. There were wide variations in the screening instruments and diagnostic tools used although the Edinburgh Postnatal Depression Scale (EPDS) was the most common instrument applied to identify PND. The prevalence of maternal PND ranged from 4.0% to 63.9%, with Japan and America recording the lowest and highest rates, respectively. Within continents, a wide variation in reported prevalence was also found. The reported rates of maternal PND in Malaysia were much higher than that previously documented with a range of 6.8–27.3%. This review indicated that the widely cited prevalence of maternal PND of 10–15% underestimates rates of PND worldwide. The reasons for this variability may not be fully explained by review methods. Future studies should evaluate the nature of women’s PND experiences across cultures to explain these wide variations.